39 x 9 = 351
Chat with our AI personalities
Original Equation: 4x + 9x = 39 Factor: x(4+9) = 39 Add: x(13) = 39 Divide: x = 3 Check: 4(3) + 9(3) = 12 + 27 = 39 = 39
2x+3=9 x
3 x 12 x 9 = 324 39 x 12 = 468
6x+9=39 The first step is subtracting 9 from both sides. This makes the equation: 6x=30 The second step is dividing by 6 on both sides. This would be the second step because x is being multiplied by 6, so you'd need to do the inverse and divide by 6. This would mean that x=5(because 30 divided by 6 equals 5). Plug it back in to check: 6∙5+9=39 30+9=39 39=39 Therefore x=5 works.
1 x 117, 3 x 39, 9 x 13 = 117